The effects of sleep deprivation on soccer skills - Pallesen, S.; Stokvold Gundersen, H.; Kristoffersen, M.; Bjorvatn, B.; Thun, E.; Harris, A. (Perceptual and Motor Skills, 2017)
Many athletes sleep poorly due to stress, travel, and competition anxiety. In the present study, we investigated the effects of sleep deprivation on soccer skills (juggling, dribbling, ball control, continuous kicking, 20 and 40 m sprint, and 30 m sprint with changes of direction). In all, 19 male junior soccer players (14-19 years old) were recruited and participated in a cross-balanced experimental study comprising two conditions; habitual sleep and 24 hours sleep deprivation. In both conditions, testing took place between 8 a.m. and 10 a.m. Order of tests was counterbalanced. Each test was conducted once or twice in a sequence repeated three times. The results revealed a negative effect of sleep deprivation on the continuous kicking test. On one test, 30 meter sprint with directional changes, a significant condition x test repetition interaction was found, indicating a steeper learning curve in the sleep deprived condition from Test 1 to Test 2 and a steeper learning curve in the rested condition from Test 2 to Test 3. The results are discussed in terms of limitations and strengths, and recommendations for future studies are outlined.